Helminth fauna of reptiles in the National Park «Smolny», Russia - Alexander А. Kirillov (Nature Conservation Research: Zapovednaâ Nauka, 2021)
Reptiles are a common component of natural biological communities. They serve as the final and paratenic hosts of helminths and play an important role in the transmission of parasites. There are very few helminthological studies covering all species of reptiles from the same locality. This paper was aimed to study the species diversity of reptile helminths in the National Park «Smolny» (Russia). In 2018‒2020 we studied the helminth fauna of five reptile species by the method of complete helminthological dissection in 19 sites of the National Park «Smolny». A total of 27 species of parasites were noted in the studied species of snakes and lizards, including 14 trematodes, two cestodes and ten nematodes. We found the richest helminth fauna in Natrix natrix (17 species) and Lacerta agilis (11). The helminth fauna was less rich in Vipera berus (eight species) and Anguis fragilis (four species). We found only two species of helminths in Zootoca vivipara. Most of the parasites (16 species) are distributed through the Palaearctic. We found one species, the nematode Oswaldocruzia filiformis, in all five studied reptile species in the National Park «Smolny». The most widespread parasite species in reptiles was the nematode Rhabdias fuscovenosa, found in 12 out of 19 studied localities in the National Park «Smolny». We conducted a comparative analysis of the helminth fauna of reptiles in the National Park «Smolny» and reptiles from other areas of the Middle Volga Region, namely Mordovia State Nature Reserve, Samara Region and the National Park «Samarskaya Luka». It was found that the parasite composition of Anguis fragilis has a maximal similarity with the ones in other regions. The helminth fauna of Natrix natrix and Zootoca vivipara in the National Park «Smolny» is less similar to other compared areas of the Middle Volga Region. The least similarity of the helminth fauna with other studied regions was found for Vipera berus and Lacerta agilis. The similarity of the helminth fauna of certain reptile species from different areas of the Middle Volga Region is caused by the specificity of helminths, as well as the geographical proximity of the studied localities and the broad distribution of parasite species of reptiles. The nematode Agamospirura minuta, juv. in Natrix natrix, as well as in Vipera berus and Lacerta agilis were found for the first time in Russia, while the trematode Pleurogenoides medians was found for the first time in such a host as Lacerta agilis. We found for the first time the nematode larvae of Physocephalus sexalatus and Physaloptera clausa in Vipera berus in Russia. We revealed that Vipera berus and Lacerta agilis are new hosts for Physaloptera clausa, juv. and Oxysomatium brevicaudatum, respectively. We noted the cestode Spirometra erinaceieuropaei, plc. in reptiles (namely Natrix natrix) from the Middle Volga region for the first time. Three parasite species (cestode Spirometra erinaceieuropaei, trematode Alaria alata and nematode Physocephalus sexalatus) found in reptiles of the National Park «Smolny», have medical and veterinary value as causative agents of potential hazardous helminthiases.